Analisis Komparatif Tindak Pidana Penipuan Dalam KUHP Kolonial dan KUHP Nasional - Delvi Paluaran; Sunardi Purwanda; Aksah Kasim; Jumardin Jumardin (Jurnal Litigasi Amsir, 2024)
The crime of fraud is a crime whose object is property. In the old colonial Criminal Code (a term for colonial products), this crime was regulated in Chapter XXV, ranging from Article 378 to Article 395, termed as "fraudulent act" or bedrog. After the new national Criminal Code (a term for indigenous products) was passed into Law Number 1 Year 2023 on the Criminal Code, does it still have similarities with the crime of fraud known in the Colonial Criminal Code? How is the difference between the two arrangements? The purpose of this study is to determine the difference in substance of the elements of the crime of fraud in the Colonial Criminal Code and the National Criminal Code, and also to determine the substance of the difference in sanctions between the crime of fraud in the Colonial Criminal Code and the National Criminal Code. This research uses normative legal research with a statutory approach and a comparative approach. Types and sources of legal materials using primary legal materials and secondary legal materials and tertiary legal materials. The results show that the difference in substance in the subjective elements is found with the presence of different terms between the phrase "whoever" and the phrase "every person". Likewise with the objective elements, namely "false dignity" and "false position", "series of lies" and "false words" and the addition in the National Criminal Code of "acknowledgment of debt". The substance of the difference in sanctions between the crime of fraud in the Colonial Criminal Code and the National Criminal Code is the focus on imprisonment for the Colonial Criminal Code while for the New Criminal Code in addition to imprisonment there is also a fine with the form of Category V fines.